Manual dexterity in dentistry: Development and evaluation of a preclinical training program - Neves, Tamíris da Costa [UNESP]; Pazos, Júlia Margato [UNESP]; Genaro, Luis Eduardo [UNESP]; Hallak, Julia Carrer [UNESP]; Garcia, Patrícia P. N. S. [UNESP] (Wiley, 2023)
Objectives: The aim of this study was to develop and evaluate the effect of a manual dexterity training program on manual dexterity, perception of self-confidence, quality of cavity preparations, and ergonomic work posture of dental students prior to preclinical training. Methods: Students in the first year of the undergraduate dentistry program (N = 63) participated in this study. The program consisted of eight phases in which students performed different types of activities. The dependent variables were: manual dexterity assessed by the modified Dental Manual Dexterity Assessment; self-confidence to perform a preclinical procedure using the VAS scale; quality of Class I cavity preparation; angular deviation from the neutral position of the neck, trunk, wrist and distance between the student's eyes and the mannequin's tooth. These variables were evaluated at two different times: before and after the application of the program. The independent variable was the preclinical manual dexterity training program. After meeting the assumption of normality, the paired t-Student test was performed, the significance level was 5%. Results: The results showed a statistically significant difference in relation to manual dexterity (p < 0.001), self-confidence (p < 0.001), quality of cavity preparations (p < 0.001), distance from the eyes of the student/mannequin (p < 0.001), deviation angle of the neutral position of the trunk (p = 0.007) and wrists (p < 0.001), with better results in posttraining. Conclusion: It was possible to conclude that, in general, the proposed training positively influenced the self-confidence, dexterity, quality of work, and ergonomics of the evaluated students.
Keywords: dental students; manual dexterity; self-confidence